Screening for Adolescent Alcohol Use in the Emergency Department: What Does It Tell Us About Cannabis, Tobacco, and Other Drug Use?. (12th May 2019) - Spirito, Anthony; Bromberg, Julie R.; Casper, T. Charles; Chun, Thomas; Mello, Michael J.; Mull, Colette C.; Shenoi, Rohit P.; Vance, Cheryl; Ahmad, Fahd; Bajaj, Lalit; Brown, Kathleen M.; Chernick, Lauren S.; et al.
Abstract: Background: The pediatric emergency department (PED) represents an opportune time for alcohol and drug screening. The National Institute of Alcohol Abuse and Alcoholism (NIAAA) recommends a two-question alcohol screen for adolescents as a predictor of alcohol and drug misuse. Objective: A multi-site PED study was conducted to determine the association between the NIAAA two-question alcohol screen and adolescent cannabis use disorders (CUD), cigarette smoking, and lifetime use of other drugs. Methods: Participants included 12–17-year olds ( n  = 4834) treated in one of 16 participating PEDs. An assessment battery, including the NIAAA two-question screen and other measures of alcohol, tobacco and drug use, was self-administered on a tablet computer. Results: A diagnosis of CUD, lifetime tobacco use or lifetime drug use was predicted by any self-reported alcohol use in the past year, which indicates a classification of moderate risk for middle school ages and low risk for high school ages on the NIAAA two-question screen. Drinking was most strongly predictive of a CUD, somewhat weaker for lifetime tobacco use, and weakest for lifetime drug use. This same pattern held for high school and middle school students and was stronger for high school students over middle school students for all three categories. This association was also found across gender, ethnicity and race. The association was strongest for CUD for high school students, sensitivity 81.7% (95% CI, 77.0, 86.5) and specificity 70.4% (95% CI, 68.6, 72.1). Conclusions/Importance: A single question about past year alcohol use can provide valuable information about other substance use, particularly marijuana.